Paths to Understand and to Limit Inflammation in Transfusions. (January 2014) - Garraud, O.; Hamzeh-Cognasse, H.; Laradi, S.; Cognasse, F.
Transfusion is generally very safe. However, in a small number of cases, it leads to mild and even serious - life-threatening - hazards (most often after platelet component transfusion). In cases where no preventable accident happens (that exclude infection, chain error, malpractice, antigen-antibody conflict), the symptomatology resembles inflammation. The present essay reports on the causes of inflammation in transfusion and in which way one may intervene on the different steps of the process -from donor to patient - to limit such incidents/accidents.